Kwaterunek urzędników wojewódzkich w Zielonej Górze w roku 1950 = Accommodation for the local administration officials in Zielona Góra in 1950 - Halczak, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The administrative department of Zielona Góra was established in 1950. A small town got promoted to the rank of the department capital. That entailed the need to provide accommodation for a large band of officials. However, the overpopulated town lacked spare flats and the authorities did not have the resources to build new houses - nor even to restore or convert the old ones.
Keywords: Zielona Góra (okręg) - historia; 1945-1950; administracja lokalna